Endothelialization of electrospun polycaprolactone (PCL) small caliber vascular grafts spun from different polymer blends. Issue 12 (26th February 2014) - Pfeiffer, D.; Stefanitsch, C.; Wankhammer, K.; Müller, M.; Dreyer, L.; Krolitzki, B.; Zernetsch, H.; Glasmacher, B.; Lindner, C.; Lass, A.; Schwarz, M.; Muckenauer, W.; et al.
Abstract Small caliber vascular grafts represent a challenge to material scientists. In contrast to large caliber grafts, prostheses with diameter <6 mm, lead to increased hemodynamic disturbances and thrombogenic complications. Thus, endothelialization of small caliber grafts should create a compatible interface for hemodynamic processes. The purpose of our study was to compare different compositions of electrospun scaffolds with conventional ePTFE grafts with an inner diameter of 4 mm as well as different pre‐coatings to create an optimized physiological interface for endothelialization. Polycaprolactone, polylactide, and polyethylenglycol (PCL/PLA and PCL/PLA/PEG) electrospun grafts and ePTFE grafts were pre‐coated with blood, gelatine or fibronectin and seeded with endothelial cells from the human term placenta. Best results were obtained with fibronectin‐coated PCL/PLA/PEG grafts. Here, the number of attached viable cells was 78–81% higher than on fibronectin pre‐treated ePTFE grafts. Cells attached to PCL/PLA/PEG grafts appeared in physiological cobblestone morphology. Viability analysis showed a high cell viability of more than 98%. Fibronectin‐coated PCL/PLA/PEG grafts may be a promising improvement to conventionally used ePTFE grafts. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4500–4509, 2014.